Antitumor activity of Typhonium flagelliforme Ethanol Extract Nanoemulsion in DMBA-Induced Sprague Dawley Rats - Rini, Dian Cipta; Priosoeryanto, Bambang Pontjo; Riki Siswandi; Sutardi, Lina Noviyanti (Acta VETERINARIA Indonesiana, 2025)
Tumors are a leading cause of disease-related deaths in humans and companion animals, including dogs and cats. Typhonium flagelliforme, recognized in Indonesian traditional medicine, exhibits notable antitumor properties, such as inhibiting tumor cell proliferation and enhancing immune response. This study aimed to formulate T. flagelliforme into a nanoemulsion to improve its antitumor eflects and assess its efficacy in Sprague Dawley rats induced with the carcinogen 7,12-dimethylbenz (a) anthracene (DMBA). The nanoemulsion was formulated using the inversion phase method, and its particle size and stability were analyzed using SEM. Phytochemical screening identified active compounds, and toxicity was assessed using the brine shrimp lethality test. In vivo experiments involved five rat groups: untreated (NTC), nanoemulsion solvent (Solv), and three treatment groups receiving 25 μg/kg (TF25), 50 μg/kg (TF50), and 100 μg/kg (TF100) doses of the nanoemulsion, administered via intralesional injection. Results showed significant tumor size reduction in treatment groups compared to controls (p<0.05), with TF25 exhibiting the most eflective antiproliferative activity. Increased body weight across groups indicated low toxicity. The study concludes that T. flagelliforme nanoemulsion eflectively reduces tumor size and angiogenesis, demonstrating its potential as an antitumor agent.